PENGOLAHAN AIR LIMBAH DOMESTIK DENGAN PROSES LUMPUR AKTIF YANG DIISI DENGAN MEDIA BIOBALL - Said, Nusa Idaman; Utomo, Kristianti (Center for Environmental Technology, 2007)
Recently, the treatment process of waste water contains organic pollutant which used in Indonesia especially in Jakarta is activated sludge process. The problem is its treated water quality which frequently does not yet fulfilled to effluent standard of wastewater. Some affecting factorsÃ‚Â are hydraulic retention time (HRT) too short, the fluctuation of wastewater flow rate, unfavorable function of aeration process and also which do not less important is operational mistake caused by insufficient knowledge of operator. To overcome the mentioned problems it is needed technological innovation to increase efficiency of wastewater treatment process especially activated sludge process.Ã‚Â This paper describes the study of domestic waste water treatmentÃ‚Â using activated sludge process which is filled with bioball plastic media for attaching microorganism to increase efficiency and Ã‚Â keep stability of process.Ã‚Â Result of the study shows that within 6 hours hydraulic retention time (HRT), the removal efficiency of COD, BOD, Ammonia and Total Suspended Solids (TSS) were 78.42%, 79.41%, 61.41%, and 82.06% respectively. The most effective of sludge circulation ratio is R=0,5Q. In sludge circulation ratio R= 0,5Q, the removal efficiency of COD, BOD, organic loading coming into bioreactor, the lower Ã‚Â removal efficiency. In organic loading (BOD loading) 0.3 - 1.0 kgBOD/m3.day, the removal efficiency of BOD was 80 - 85 %.Ã‚Â Ã‚Â Kata kunci : Air limbah domestik, lumpur aktif, bioball, aerob.